Estresse e imuno modulação por beta-glucano em Pacu (Piaractus mesopotamicus) - Sabioni, Rafael Estevan [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Fish farming intensification may increase the frequency and intensity of stressful situations, decreasing productivity. The stress response is established in order to maintain homeostasis, but its extension may decrease the ability of defense, by the action of cortisol, exposing fishes to pathogens. In this sense is studied the strategic use of molecules that have the ability to stimulate the immune system, such as ?-glucan, protecting the fish before stressful events. The immunity of fish is similar to that of mammals and can be monitored through the analysis of some components such as lysozyme, complement system proteins and white cells profile. Pacu was chosen as biological model by its productive characteristics. In this context three experiments were established. The first evaluated the action of ?-glucan-containing feed against a stress condition simulated by intraperitoneal injection of hydrocortisone. The second and third ones tested the action of the?-glucan against the elevation of exogenous and endogenous cortisol, respectively, and Aeromonas hydrophila inoculation. In the overall results, the protocols used to increase endogenous and exogenous cortisol were efficient, however, due to induce cortisol levels above the physiological, it is recommended to use a dose lower than 10mg / g hydrocortisone for the exogenous. The use of 0.5% ?-glucan reduced cortisol levels, suggesting attenuation of hormonal response, and activate leukocyte function with 0.1% and 0.5%, administered for 15 and 10 days, respectively, even with reduction of leukocytes number by cortisol action. The concentration of lysozyme and complement system activity responded to infection. increasing 24 hours after inoculation simultaneously

A intensificação da piscicultura pode aumentar a frequência e intensidade de situações estressantes, diminuindo a produtividade. A resposta de estresse se estabelece com o fim de manter a homeostase, porém seu prolongamento pode diminuir a capacidade de defesa do organismo, por ação do cortisol, o expondo à patógenos. Neste sentido estuda-se a ação estratégica de moléculas que têm a capacidade de estimular o sistema imune, a exemplo do ?-glucano, protegendo os peixes antes de manejos. A imunidade dos peixes, semelhante à dos mamíferos, pode ser acessada por meio da análise de componentes celulares e moleculares. O pacu, por suas características produtivas, foi escolhido como modelo biológico. Neste contexto foram desenvolvidos três experimentos. O primeiro avaliando a ação da alimentação contendo ?-glucano frente à simulação de estresse por injeção intraperitoneal de hidrocortisona e o segundo e terceiro, testando a ação do imunoestimulante frente à elevação do cortisol exógeno e endógeno, respectivamente, e inoculação com Aeromonas hydrophila. Na análise geral dos resultados, os protocolos de elevação do cortisol endógeno e exógeno foram eficientes, porém, por induzir níveis acima dos fisiológicos, recomenda-se usar dose menor que 10?g/g para o segundo. O uso de 0,5% de ?-glucano reduziu os níveis de cortisol, sugerindo atenuação da resposta hormonal, além de ativar a função leucocitária com 0,1% e 0,5%, administrados por 15 e 10 dias, respectivamente, mesmo com diminuição do número de leucócitos por ação do cortisol. A concentração de lisozima e atividade do sistema complemento responderam à infecção. aumentando simultaneamente 24 horas após inoculação
Keywords: Peixe; Pacu (Peixe); Stress (Fisiologia); Estimulante; Levedos; Fishes